Mengungkap Komponen Kritis Untuk Keberhasilan Kota Desain Kreatif - Andi Sahputra Depari (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2023)
In the 21st century, numerous phenomena have significantly influenced spatial behavior, particularly in urban areas. These changes in behavior are attributed to various factors, one of which is the substantial increase in urban residents since the industrial era. The surge in urban population has led to a state of disorder within cities, resulting in the emergence of slums and a strain on social and cultural dynamics. In response to these challenges, it is essential to adopt an approach that can effectively engage urban communities in the proper development of cities. One such approach, endorsed by UNESCO as a modern urban concept, is the Creative City concept. The Creative City is believed to empower communities by providing them with opportunities for active participation in city development, facilitated by diverse facilities and activities. Consequently, researchers are conducting a case study on Medan City to identify key elements, particularly from a social perspective, that define a city as a creative city of design. The method employed in this study is Multi-Criteria Decision Analysis (MCDA), which will prioritize the main indicators to assess the factors involved. By analyzing survey data and conducting a thorough analysis, it has been determined that human orientation, exhibition space, and professional exchange are the top three social factors contributing to Medan's transformation into a creative city of design. The findings of this study can significantly contribute to shaping the design of a creative city of design and provide valuable support to stakeholders in formulating policy recommendations for realizing a creative city of Design.